The Effectiveness of Behavioral Counseling in Reducing Temperamental Behavior among Students at MTsS MUQ Pagar Air - Putri Rizka Humaira; Fakhri Yacob (Universitas Negeri Medan, 2026)
This study aims to examine the effectiveness of behavioral counseling in reducing students' temperamental behavior. The research employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The subjects consisted of 7 seventh-grade students of MTsS MUQ Pagar Air Banda Aceh who were selected through purposive sampling based on their high levels of temperamental behavior. Data were collected using a questionnaire covering the aspects of emotionality, activity, and sociability. Data analysis was conducted using descriptive statistics, the Shapiro-Wilk normality test, paired sample t-test, and N-Gain analysis with the assistance of IBM SPSS Statistics version 25. The results showed that the mean pretest score of 66.86 decreased to 25.71 in the posttest. The paired sample t-test revealed a significance value of 0.000 < 0.05, indicating a significant difference before and after the treatment. The average N-Gain score of 0.61 was categorized as moderately effective. Therefore, behavioral counseling using the operant conditioning technique was found to be effective in reducing students' temperamental behavior. These findings are expected to encourage readers to further analyze the role of behavioral counseling services as an appropriate intervention strategy in helping students develop self-control and more adaptive behavior within the school environment.